5z-2=6z

Simple and best practice solution for 5z-2=6z equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5z-2=6z equation:


Simplifying
5z + -2 = 6z

Reorder the terms:
-2 + 5z = 6z

Solving
-2 + 5z = 6z

Solving for variable 'z'.

Move all terms containing z to the left, all other terms to the right.

Add '-6z' to each side of the equation.
-2 + 5z + -6z = 6z + -6z

Combine like terms: 5z + -6z = -1z
-2 + -1z = 6z + -6z

Combine like terms: 6z + -6z = 0
-2 + -1z = 0

Add '2' to each side of the equation.
-2 + 2 + -1z = 0 + 2

Combine like terms: -2 + 2 = 0
0 + -1z = 0 + 2
-1z = 0 + 2

Combine like terms: 0 + 2 = 2
-1z = 2

Divide each side by '-1'.
z = -2

Simplifying
z = -2

See similar equations:

| 5n+3(2n-8)=2(n+6) | | 4N+32=3N | | 6(-.5)+1=m | | 4/5x-12=-32 | | -5x-8+3x=-18 | | -3x^2+18x-27=0 | | .6x-21=15 | | .3x-4=.75x+1 | | 3x+5=3x+55 | | 6x-3(2x+2)=2x-3 | | 3x+2(2x+15)=107 | | 4.5/(g+2)=3/(0.5g-1) | | 6(6v+5)=14+5v | | 0.5=0.4y-0.25(90) | | 45+60x= | | 12x=4x+2 | | 3x(2-3)=x | | 3(-.5)-(-.5+1)=x | | 4(n-1)-(4-9n)=12n | | .08x=.03(x+200)-4 | | -x-5=13 | | (x-5)(x+6)/(x-3)=0 | | 3x+(2x+15)=107 | | 10(5+x)=14(y-3) | | .3(x+14)=.1(x+40) | | -2=6+10 | | 9x+5-9x=-20 | | 2=w/5-18 | | 37x+20(20-x)=7.06 | | 7c-2= | | (1.2x+6)/0.8x=3.5 | | 6x-10+3x=35 |

Equations solver categories